คุณธรรมจำเป็นสำหรับโรงเรียนชายขอบทางภาคเหนือ: The Moral in the Marginalized Schools Along the Northern Borders - Saijittra Nisai; Others สายจิตรา นิสาย และคณะ; Mallika Karakasikhawitee มัลลิกา การกสิขวิธี; Nart Srilapo นารท ศรีละโพธิ์ (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2020)
คุณธรรมเป็นสภาพคุณงามความดีทางความประพฤติและจิตใจ คุณลักษณะนิสัยหรือหลักของการควบคุมพฤติกรรมของบุคคล โดยสอดคล้องกับมโนธรรมที่ตนยึดถือตามมาตรฐานทางสังคม เกี่ยวข้องกับการกระทำที่ตระหนักรู้และเหมาะสมกับหลักศีลธรรมที่ถูกต้องดีงาม ซึ่งได้รับการสั่งสมหรือปฏิบัติตามกันมารวมทั้งเป็นสิ่งที่ผู้อื่นและสังคมยอมรับได้ การสร้างความตระหนักและปลูกฝังจิตสำนึกเกี่ยวกับคุณธรรมให้กับผู้เรียน ในโรงเรียนจึงเป็นสิ่งที่จำเป็นอย่างยิ่ง โดยเฉพาะโรงเรียนชายขอบทางภาคเหนือ ซึ่งมีสภาพนักเรียนที่มีความเสี่ยงและเปราะบางมากกว่าโรงเรียนทั่วไป เนื่องจากความแตกต่างของสภาพแวดล้อมและบริบทของแต่ละพื้นที่ความแตกต่างทั้งทางด้านชาติพันธุ์ ภาษา เศรษฐกิจ สังคม ศาสนาและประเพณีวัฒนธรรม ซึ่งล้วนเป็นปัจจัยสำคัญที่ส่งผลต่อคุณธรรมของผู้เรียน บทความวิชาการนี้จึงนำเสนอคุณธรรมจำเป็นสำหรับโรงเรียนชายขอบทางภาคเหนือของประเทศไทยเพื่อเป็นแนวทางการพัฒนาคุณธรรมและพัฒนานักเรียนให้เป็นพลเมืองที่ดีของสังคมต่อไป Moral is a good virtue governing a person’s behavior and mind, personality trait and principles of behavioral conduct. Moral is coherent with a person’s conscience based on the society standards. It connects with a mindful awareness and ability to distinguish between right and wrong according to society’s ethical standards that having been cultivated or practiced by people in the society. It is so crucial that moral needs to be cultivated and developed an awareness for students in schools, especially in the marginalized schools along the northern borders which are likely to include a higher number of at-risk and vulnerable groups of students. Due to the demographic and contextual differences such as the racial, linguistic, economic, social, religious and cultural varieties are all the major factors contributing to the moral growth of learners, this paper proposes the moral development necessary for students in the marginalized schools located in the northern borders of Thailand in order to provide a guideline for moral development and for developing the students to be the good citizens of the nation.